Pengaruh Intervensi Apoteker terhadap Tingkat Bahaya Drug-Related Problems pada Pasien Geriatrik Rawat Inap - Margarita Krishna Setiawati; Nanang Munif Yasin; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Geriatric patients are at high risk of Drug-Related Problems (DRPs) associated with multimorbidity, physiologic changes, and pharmacologic alterations, that caused by the aging process. The pharmacist plays an important role in optimizing the effectiveness and safety of the patient’s drug therapies. This study aims to know the effect of pharmacist intervention in reducing the harmful levels of DRPs and to know the factors associated with the reduction of DRPs harm level in hospitalized geriatric patients. This research uses quasi-experimental study with a one-group pretest and posttest design. This research was conducted in Panti Rapih Hospital between March-April 2021, with patients’ inclusion criteria of ≥ 60 years old, with internal diseases cases, and identified DRPs in the therapy. The exclusion patient criteria are hospitalized in the intensive unit and Covid-19 ward. A pharmacist reviewed patient drug therapy, identified and solved DRPs. The harm level of DRPs was compared before and after pharmacist interventions. The harm level of DRPs was determined through professional adjustment according to The Harm Associated with Medication Error Classification tools, then analyzed using Wilcoxon test with a level of confidence 95%. Factors of age, the number of drugs received by the patient, comorbidities, and acceptance of the intervention were investigated for their effect on reducing the harm level of DRPs using a multivariate logistic regression test. A total of the research subject were 28 inpatients, with 47 DRPs identified. The most frequent DRPs were adverse drug reactions  (27,66%). Among all interventions, 77,36% of them were accepted with full implementation. The pharmacist intervention resulted in a significant reduction in the harm level of both potential and actual DRPs (p < 0,05). A factor of the number of drugs received by patients and acceptance of pharmacist intervention was associated with the reduction of the harm level of DRPs (p < 0,05). This study shows that multidisciplinary collaboration is needed in the care of geriatric patients.